دور الأعوان التنفيذيون في الرقابة على تحفيز النفقات العمومية - بن شنذيخ, أمال (My University, 2020)
This study aims to identify public accounting and how to implement expenditures and control them in Algeria, by addressing the agents assigned to implement public expenditures and its various stages, as well as getting to know the various oversight bodies, and through our study the case of the College of Economic, Commercial and Management Sciences we will try to drop the study The theory to the field chapter and follow the various procedures for implementation and control of college expenditures, Mostaganem University, as it is one of the public institutions of an administrative nature that cost the college budget in Mostaganem University and its implementation. Among the most important results reached is that the state strives to focus on optimizing the use of its financial, material and human resources through laws, regulations and instructions in progress, in addition to the large role of the person commanding the exchange and the public accountant in implementing public expenditures and controlling them.
دراسة حالة كلية العلوم الاقتصادية والتجارية وعلوم التسيير
Keywords: الأعوان التنفيذيون – المحاسبة العمومية – النفقات العمومية – الرقابة المالية